Effects of salinity and broad-range antibiotics on oxalate production, transport, and degradation in Poecilia latipinna - Felicia Vimala Rajan; Carol Bucking (PLoS ONE, 2026)
Oxalate is an anion that readily binds calcium and is thought to contribute to osmoregulation. This study investigated how environmental salinity influences oxalate homeostasis in euryhaline sailfin mollies ( Poecilia latipinna ), with a focus on the interplay between microbial symbiosis and host transport processes. Gut microbiome profiling demonstrated regional specialization, with the posterior intestine enriched in oxalate-degrading bacterial families. Community shifts across salinities suggests functional redundancy and resilience, ensuring maintenance of oxalate-catabolizing capacity. Antibiotic treatment disrupted this system, impairing microbial degradation and causing systemic oxalate stress. Oxalate concentrations were also measured in the liver, intestine, and kidney, organs central to oxalate metabolism, under freshwater and seawater conditions. Salinity induced a redistribution of oxalate among these organs, with the gut assuming an auxiliary excretory role in seawater. This functional shift parallels mammalian colon physiology and highlights the gut’s role in balancing ion and oxalate flux. Expression analyses of the oxalate transporters SLC26A3 (solute carrier family 26, member 3) and SLC26A6 (solute carrier family 26, member 6) revealed organ-specific and salinity-dependent regulation. Both transporters displayed distinct responses to seawater exposure, indicating specialized roles in oxalate handling. These patterns suggest coordinated but nonredundant mechanisms that govern absorption and secretion, linking salt transport with oxalate clearance. These findings underscore the microbial contribution to oxalate balance and reveal that osmoregulatory challenges shape gut microbial composition and function. Collectively, this study presents the first comprehensive analysis of oxalate metabolism in a euryhaline teleost and demonstrates a coordinated host–microbe system that mitigates oxalate accumulation across salinities. By integrating metabolic and osmoregulatory demands, P. latipinna reallocates excretory function from kidney to gut and leverages microbial symbiosis to preserve homeostasis. These findings expand our understanding of teleost physiology and highlight oxalate metabolism as a critical axis of environmental adaptation.